118k views
1 vote
Given: F(x) = 2x - 1; G(x) = 3x + 2; H(x) = x2
Find G[H(1)).

User Kiren S
by
4.3k points

1 Answer

3 votes

Answer:

5

Explanation:

The question ask for G[H(1)] so we have to find the H(1) first and it doesn't ask for anything about the F(x) so we don't have to worry about it. I dont know if H(x) = x*2 or x^2 but i'll consider it as x^2.

H(1) = (1)^2 Plug in 1 for x

H(1) = 1

since we find H(1) = 1 we just put it as G(1) because its same as G[H(1)]

G(1) = 3x + 2

G(1) = 3(1) +2 =5

G(1) = G[H(1)] = 5

User Todoy
by
4.7k points